The Role of Soluble HLA-G Serum Level in Therapeutic Response of Chronic Myeloid Leukemia Patients - Zainab Khalid Khaleel; Hayfaa Salman Al-Hadithi; Asaad AbdulAmeer Khalaf; Omran Sukar Habib (Indian Journal of Forensic Medicine & Toxicology, 2022)
Human leukocyte antigen-G molecules (HLA-G) have been suggested to play a role in immune evasion and progression of different malignancies by their tolerogenic activity, through interaction with inhibitory receptors on surface of immune cells.The aim is to evaluate the role of the s HLA-G serum level in the prognosis and therapeutic responses to TKIs in CML patients.Serum level of soluble HLA-G was measured for a total of 61 adult patients with CML, who were on regular TKI for at least 6 months whom attended the out-patient’s clinic of the Hematology Center in Basra, compared with 20 apparently healthy controls matched in ages and sexes to the patients using Enzyme Linked Immuno-Sorbent Assay (ELISA) technique.Serum levels of HLA-G in CML patients was significantly higher than that in healthy controls (p=0.006). Elevated serum level of s HLA-G was significantly correlated with sex, BMI, duration of disease, Sokal scoring system.On the other hand, low s HLA-G serum level was significantly correlated with event free status (EF) of CML patients.Lower level of serum soluble HLA-G in CML patients compared to healthy controls and it might be proved as a prognostic biomarker for CML patients.